Alterations in the heart rate and activity rhythms of three orbital astronauts on a space mission. (January 2015) - Liu, Zhizhen; Wan, Yufeng; Zhang, Lin; Tian, Yu; Lv, Ke; Li, Yinghui; Wang, Chunhui; Chen, Xiaoping; Chen, Shanguang; Guo, Jinhu
Abstract: Environmental factors in space are dramatically different from those on Earth. The spaceflight environment has been known to influence human physiology and behavior on orbital missions. In this study, we investigated alterations in the diurnal rhythms of activity and heart rate of three Chinese astronauts on a space mission. An analysis of the heart rate data showed a significant decrease in heart rate amplitudes during flight in all three subjects. The heart rate amplitudes of all the three astronauts were significantly dampened during flight, and the minimum as well as the maximum value of heart rate increased after flight. A phase shift in heart rate was observed in one of the three astronauts after flight. These results demonstrate the influence of spaceflight on heart physiology and function. In addition, a significant decrease in body trunk activity and rhythmicity occurred during flight, demonstrating that the spaceflight environment disturbs motion adaptation and diurnal activity rhythms. Highlights: Spaceflight elicited reduction in the amplitude of heart rate in three astronauts. The minimum data of heart rate vary in different individuals under microgravity. Orbital flight shows long-term postflight impacts on heart rate and activity. Microgravity might lead to decrease in the trunk activity.